How do specimen preparation and crystal perfection affect structure factor measurements by quantitative convergent‐beam electron diffraction?. Issue 2 (29th March 2017) - Peng, Ding; Nakashima, Philip N. H.
Abstract : The influence of specimen preparation and crystal perfection on the measurement of structure factors and bonding by quantitative convergent‐beam electron diffraction is assessed in detail. Whilst CeB6 is the subject of this study, the findings and methods apply to all hard brittle crystalline materials. Abstract : The effectiveness of tripod polishing and crushing as methods of mechanically preparing transmission electron microscopy specimens of hard brittle inorganic crystalline materials is investigated via the example of cerium hexaboride (CeB6 ). It is shown that tripod polishing produces very large electron‐transparent regions of very high crystal perfection compared to the more rapid technique of crushing, which produces crystallites with a high density of imperfections and significant mosaicity in the case studied here where the main crystallite facets are not along the natural 001 cleavage planes of CeB6 . The role of specimen quality in limiting the accuracy of structure factor measurements by quantitative convergent‐beam electron diffraction (QCBED) is investigated. It is found that the bonding component of structure factors refined from CBED patterns obtained from crushed and tripod‐polished specimens varies very significantly. It is shown that tripod‐polished specimens yield CBED patterns of much greater integrity than crushed specimens and that the mismatch error that remains in QCBED pattern matching of data from tripod‐polished specimens is essentially nonsystematic in nature. This stands in contrast to QCBED using crushed specimens and lends much greater confidence to the accuracy and precision of bonding measurements by QCBED from tripod‐polished specimens.